Possible land management uses of common cypress to reduce wildfire initiation risk: a laboratory study. (15th August 2015) - Della Rocca, G.; Hernando, C.; Madrigal, J.; Danti, R.; Moya, J.; Guijarro, M.; Pecchioli, A.; Moya, B.
Abstract: Accurate determination of flammability is required in order to improve knowledge about vegetation fire risk. Study of the flammability of different plant species is essential for the Mediterranean area, where most ecosystems are adapted to natural fire but vulnerable to recurrent human-induced fires, which are the main cause of forest degradation. However, the methods used to evaluate vegetation flammability have not yet been standardized. Cupressus sempervirens is a native or naturalized forest tree species in the Mediterranean area that is able to tolerate prolonged drought and high temperatures. The aim of this study was to characterize the flammability of C. sempervirens var. horizontalis at particle level by using different bench-scale calorimetry techniques (mass loss calorimeter, epiradiator and oxygen bomb) to determine the main flammability descriptors (ignitability, sustainability, combustibility and consumability) in live crown and litter samples. Our findings indicate that this variety of cypress is relatively resistant to ignition because of the high ash content, the high critical heat flux, the high time to ignition displayed by both crown and litter samples and the ability of the leaves to maintain a high water content during the summer. We also discuss the possibility of exploiting some morphological, functional and ecological traits of the species to construct a barrier system (with selected varieties of cypress) as a promising complementary land management tool to reduce the fire spread and intensity in a Mediterranean context. Highlights: The flammability of Cupressus sempervirens has been fully characterized. Two contrasted bench-scale methodologies have been used to ratify the results. Cypress showed low ignitability and consumability and high sustainability and combustibility. The low ignitability of C. sempervirens suggests a potential resistance to moderate wildfires. Cypress stands could be a promising land management tool to reduce the wildfire initiation risk.